ANALISIS KESALAHAN LINGUITIK HASIL TERJEMAHAN GOOGLE TRANSLATE DARI TEKS BAHASA INGGRIS KE DALAM BAHASA INDONESIA - Sri Utaminingsih; Diyan Andriani (JURNAL EDUSCIENCE, 2022)
Currently, various ICT-based automatic translation machines are available to help translate foreign language texts, especially for those who are less proficient in foreign languages, one of which is Google's Google Translate. A student, especially one who is not from a non-English study program, in doing translation tends to use machine translation; â€œGoogle Translateâ€ and take advantage of its linguistic competence. The translation is done with or without the machine, will cause errors in a certain form. The ability to translate is one of the language competencies needed by academics. This study aims to analyze linguistic errors resulting from the translation of the Google Translate machine from English into Indonesian texts for students of the Indonesian Language and Literature Study Program STKIP YPM Bangko on the syntactic and semantic aspects. This study uses the Mix Method method which combines quantitative and qualitative research methods. The results showed that most of the students were wrong in translating the given text. Most of the translation errors are in the form of syntax errors with an average percentage of 73% while semantic errors are 27%.